plzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzzz helpppppppppppppp

Asked by sumitsial | 24th Jan, 2010, 07:50: PM

Expert Answer:

9x2-9(a+b)x +(2a2 +5ab +2b2)=0

A = 9, B = -9(a+b), C = (2a2 +5ab +2b2)

Solution of the above quadratic equation,

x = {-B±(B2-4AC)}/2A

={9(a+b)±(81(a+b)2-4x9x(2a2 +5ab +2b2))}/18

= {9(a+b)±(81a2 + 162ab + 81b2 - 72a2 - 180ab -72b2))}/18

= {9(a+b)±(9a2 - 18ab + 9b2)}/18

= {9(a+b)±(9(a-b)2)}/18

= {9(a+b)±(3(a-b))}/18

Hence the solution is,

x = (2a+b)/3 and (a+2b)/3

Regards,

Team,

TopperLearning.

Answered by  | 24th Jan, 2010, 10:18: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.